Vzpostavitev sodobne opazovalne mreže za ocenitev rudarske škode - Todorović, Ranko T. (Geodetski vestnik, 1997)
The aim of the observational geodetic network is to detect the movements and deformations of the Earth's surface treatened by subterranean mining. This article describes test measurements upon the introduction of GPS technology in the existing terrestial observational network at the Velenje coal mine.
Keywords: geodezija; GPS; izmera; opazovalne mreže; rudarstvo; transformacija